The Infraoptic or Infrachiasmatic Course of the Anterior Cerebral Artery Emerging an Elongated Internal Carotid Artery - Dragoş Ionuţ Mincă; Mugurel Constantin Rusu; Petrinel Mugurel Rădoi; Alexandra Diana Vrapciu; Sorin Hostiuc; Corneliu Toader (Tomography, 2022)
(1) Background: The normal A1 segment of the anterior cerebral artery (ACA) has a supraoptic course. The proximal infraoptic course of an A1 segment leaving the internal carotid artery (ICA) near the origin of the ophthalmic artery is a rare possibility. This study aimed to determine the prevalence and detailed anatomy of infraoptic A1 segments. (2) Methods: We retrospectively studied 145 computed tomography angiograms from 92 male and 53 female cases, with ages varying from 61 to 78 y.o. (3) Results: In 21/145 cases, infraoptic or infrachiasmatic horizontal-medial courses of A1 segments that emerged distally from the ICA were found. Distal infraoptic A1 segments were bilateral in 16/145 cases and unilateral in 3/145 cases. Infrachiasmatic A1 segments were found bilaterally in 2/145 male cases. All the infraoptic/infrachiasmatic A1 segments left long ICAs with low bifurcations. In 7/34 sides with distal infraoptic or infrachiasmatic A1 segments, supracarotid courses were present. In one female, the right A1 segment had an anterior supraclinoid, supracarotid and infraoptic course. In two female cases with a bilateral distal infraoptic A1, the segment was almost contacting the respective posterior cerebral artery. (4) Conclusions: In cases with dolicho(ectatic) ICAs, the A1 segments could have infraoptic and supracarotid courses the neurosurgeons should be aware of.